The evolving properties of the corona of GRS 1915+105: a spectral-timing perspective through variable-Comptonization modelling. Issue 3 (12th May 2022) - García, Federico; Karpouzas, Konstantinos; Méndez, Mariano; Zhang, Liang; Zhang, Yuexin; Belloni, Tomaso; Altamirano, Diego
ABSTRACT: The inverse Compton process by which soft photons are up-scattered by hot electrons in a corona plays a fundamental role in shaping the X-ray spectra of black hole (BH) low-mass X-ray binaries (LMXBs), particularly in the hard and hard-intermediate states. In these states, the power-density spectra of these sources typically show Type-C low-frequency quasi-periodic oscillations (QPOs). Although several models have been proposed to explain the dynamical origin of their frequency, only a few of those models predict the spectral-timing radiative properties of the QPOs. Here, we study the physical and geometrical properties of the corona of the BH-LMXB GRS 1915+105 based on a large sample of observations available in the RXTE  archive. We use a recently developed spectral-timing Comptonization model to fit simultaneously the energy-dependent fractional rms amplitude and phase-lag spectra of the Type-C QPO in 398 observations. For this, we include spectral information gathered from fitting a Comptonization model to the corresponding time-averaged spectra. We analyse the dependence of the physical and geometrical properties of the corona upon the QPO frequency and spectral state of the source, the latter characterized by the hardness ratio. We find consistent trends in the evolution of the corona size, temperature, and feedback (the fraction of the corona photons that impinge back on to the disc) that persist for roughly 15 yr. By correlating our observations with simultaneous radio-monitoring of the source at 15 GHz, we propose a scenario in which the disc–corona interactions connect with the launching mechanism of the radio jet in this source.